NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU PEPELING JEUNG PANGGEUING KARYA KH ACENG ZAKARIA - Saefullah, Agus Susilo; Hidayat, Rahman (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2024)
This research aims to identify and analyze the values ​​of character education contained in the book "Pepeling jeung Panggeuing" by KH Aceng Zakaria. This book, written in Sundanese, is a collection of advice from a leading scholar who has significantly contributed to education and moral development in society. The language used in this book is very persuasive and easy to understand, especially for the people of West Java. A qualitative approach with content analysis was used in this research to understand the moral and ethical messages contained in the book. Data was collected through an in-depth study of book texts and secondary references related to character education theory. The research results reveal several core values ​​taught in this book, namely the book "Pepeling jeung Panggeuing" which plays an important role in shaping readers' character through applicable and relevant advice. The book "Pepeling jeung Panggeuing" contains a collection of advice that makes people aware of negative actions and awakens the human mind so that they can rise from laziness and be more optimistic in living their lives. This book contains character education values, including religious character education, cooperation, tolerance, hard work and generosity. The implication is that this book can be used as a reference in the character education curriculum in schools and as a guide for families and communities in developing the morals of the younger generation. This research recommendation includes the development of a more integrative and adaptive educational program based on the values ​​contained in this book